Optimalisasi Nilai Kekuatan Bending Pembuatan Komposit UPRS - Cantula 3D dengan Metode Taguchi - Lujeng Widodo; Teguh Wiyono (Politeknosains, 2016)
The needs industry on composite materials made from natural fibers with a quality that meets the standards is expected. Because of the existing raw materials can not meet the needs of material is strong, lightweight, inexpensive and environmentally friendly.Number Variations of thread, Total Torsion, Structure and Percentage Resin wicker is used as a combination of factor levels. Composite tensile testing refers to the , for bending testing refers to the standard ASTM D 790-97. The statistical testing performed; Normality, homogeneity, Anova, SNR and different test. To simplify ANOVA the writer used Taguchy methode. The results show that the fabric construction, especially the number of torsion and resin concentration effect on tensile strength while the type and concentration of resin wicker affect tensile strength while the optimal value is achieved for Pull strength 1,02 MPa. At the factor level combination Ne1 0.8, Twist 500, Woven with 16 cards and 35% resin concentration.